PENINGKATAN PENGALAMAN PENGGUNA: PERANCANGAN ANTARMUKA APLIKASI JUWANA DENGAN PENDEKATAN USER CENTERED DESIGN: ENHANCING USER EXPERIENCE: DESIGNING JUWANA APP INTERFACE WITH USER CENTERED DESIGN APPROACHD - Surya Saputra, Surya Saputra; Muhammad, Meizano Ardhi; Pratama, Mahendra; Septama, Hery Dian; Martinus, Martinus (BAROMETER, 2024)
Fast and stable internet access has become an essential requirement in daily activities. To meet this need, subscribing to internet packages has emerged as a viable solution. Therefore, the development of a user interface (UI) for a mobile application that facilitates internet package subscriptions is crucial. This study aims to design the user interface of a mobile application called Juwana, which allows users to easily purchase internet subscription packages and enhance user satisfaction. The User Centered Design (UCD) method was employed in this research. The UI design of the Juwana application was developed by analyzing user requirements, designing solutions based on those requirements, and conducting usability testing using Maze and the System Usability Scale (SUS). The results of this study present the design of the Juwana application's user interface, consisting of 13 interfaces. Maze testing indicated that all testing scenarios yielded the expected outcomes. The SUS testing results showed that the Juwana application design prototype obtained an average score of 75.7 with a grade scale of C, a Good adjective rating, and fell within the Acceptable category. Based on the findings and discussions of this research, it can be concluded that the user interface design of the Juwana application, developed using the User Centered Design (UCD) method, meets user needs and preferences. The design facilitates the process of purchasing internet subscription packages and enhances user satisfaction.